Application of Mouse Antibodies to Somatic Antigen for Detection of Salmonella enteritidis by Competitive ELISA - Hochel, Igor; Jeníková, Gabriela; Dursi, Cinzia Franceska; Pazlarová, Jarmila; Girotti, Stefano; Demnerová, Katerina (Food and agricultural immunology, 2001)
Competitive ELISA estimation based on application of polyclonal mouse antibodies to somatic antigen O:9, 12 was developed. The optimization of the protocol is reported. The optimal concentration of immobilized somatic antigen O:9, 12 was found to be 4.9 2 10 4 cells ml −1 ; optimal concentration of mouse IgG was 6.25 w g ml −1 ; and the optimal concentration of peroxidase labelled antibody to mouse IgG was 8 w g ml −1 . The tested antibody exhibited neither cross reactions with chosen strains (serotypes) of salmonellas group 04 (B), 07 (C 1 ), 08 (C 2 -C 3 ), nor with members of Enterobacteriaceae: Escherichia coli, Klebsiella pneumonia, Citrobacter freundii and non-fermenting bacterium Pseudomonas fluorescens. Application of chemiluminiscent substrates increased the sensitivity of S. enteritidis detection up to three times. Competitive ELISA tested on model samples produced results comparable with standard cultivation techniques for Salmonella spp.